Intelligent Crime Analysis System Using Pyspark - A. , Ponmalar; P., Leela Jancy; V., R. Barath Kumar; B.K. , Akshathaah; P. , Pavithra (International Journal of Psychosocial Rehabilitation, 2020)
Crime analysis is one of the most important activities of the majority of the intelligent and law enforcement organizations all over the world. Generally they collect domestic and foreign crime-related data (intelligence) to prevent future attacks and utilize a limited number of law enforcement resources in an optimum manner. A major challenge faced by most of the law enforcement and intelligence organizations is efficiently and accurately analyzing the growing volumes of crime-related data. The vast geographical diversity and the complexity of crime patterns have made the analyzing and recording of crime data more difficult. Data mining is a powerful tool that can be used effectively for analyzing large databases and deriving important analytical results. This paper presents an intelligent crime analysis system that is designed to overcome the above-mentioned problems. The proposed system is here; we find weather analysis along with the crime that happened, and we proposed Pyspark here to store large amounts of data for crime analysis. The proposed system consists of a rich and simplified environment that can be used effectively for processes of crime analysis.